A study on factors affecting reporting patient safety incident in Kajang Hospital, Malaysia - Roselan, Jalilah Binti
Patient safety is a significant concern on a global scale, and there are ongoing efforts to address the challenge of critical incident reporting. Incident reporting system are widely considered effective instruments for enhancing patient safely and addressing concerns effectively, making them an essential initial step in developing a program in patient safety. Through incident reporting, various kinds of errors can be traced and discussed among health professionals and preventive mechanisms can be designed. However, incident reporting is not fully utilized in hospitals, despite its potential to improve healthcare provision and underreporting is still prevalent across many countries including Malaysia. This substantially impedes the surveillance of patient safety trends and advancements, which is essential for steering development efforts. Therefore, this research aims to determine the level of reporting patient safety incident and to examine the factors that influence the reporting of patient safety incidents among healthcare personnel at Kajang Hospital. The study used an analytic cross-sectional quantitative approach, incorporating a two-part online questionnaire consisting of a demographic component and a 20-item Incident Reporting Culture Questionnaire (IRCQ) subdivided into four main factors; learning from error, feedback provision in system design, confidentiality & anonymity and punitive work environment. Data were analyzed using SPSS version 23. The study population comprised of doctors and nurses working in both inpatient and outpatient clinical based departments in Kajang Hospital. The findings reveal a notable pattern of underreporting with majority of respondents (48.6%) had never reported any incidents in the preceding 12 months which implies suboptimal use of incident reporting system to report incidents in the facility and highlight the urgent necessity for an improved reporting culture as to ensure all safety incidents are being reported within the facility. Factors of learning from error had the highest mean score with majority of the respondents (89.60%) had high level of perception believing it significantly influences reporting and significant positive correlation (r=0.151, p<0.05) shown between this factor and reporting behavior. This implies that respondents highly valued incident reporting as a tool for quality improvement and expressed the need to see visible improvements stemming from reported incidents subsequently promote better reporting practices among respondents. Additionally, factors of feedback provision (r=0.142, p<0.05) as well as confidentiality & anonymity (r=0.128, p<0.05) also showed positive correlation with reporting behavior. Conversely, the punitive work environment factor showed the most significant negative correlation (r=-0.180, p<0.01) with reporting behavior. The low reporting level among healthcare personnel in Kajang Hospital necessitates improved strategies for enhancing behaviour by including the key factors identified that influence reporting behaviour among healthcare staff in Kajang Hospital. To establish a more effective and efficient incident reporting system, strategies for improving reporting behaviour should include creating a supportive environment that eliminates punitive actions, fostering an organisational learning culture, implementing a reliable feedback mechanism, and ensuring reporter confidentiality and anonymity.